Evaluasi Pendidikan Vokasi di Era Revolusi Industri 4.0 dan Society 5.0 - Wulandari, Herlina Tri; Susanto, Heri; Muhibbin, Ahmad; Susilo, Agus (Paedagogie, 2025)
The development of the Fourth Industrial Revolution and Society 5.0 has caused major changes in the world of work and education in Indonesia. In this context, vocational education plays a crucial role in preparing a quality workforce that meets market needs. This study aims to assess the vocational education system in vocational high schools by applying the Link and Match concept and in-depth learning in the vocational high school curriculum that can adapt to the needs of the current industrial and social era. The method used in this study is the CIPP (Context, Input, Process, Product) evaluation approach by collecting data through observation, interviews, questionnaires, and documentation. The findings of this study indicate that the vocational education system has made progress, as seen in the alignment between the curriculum and industry needs supported by the Link and Match program, although there are still challenges in the areas of facilities, teacher competence, and technology implementation that need to be improved. Project-based learning, internships, and teaching factories have proven effective in improving students' readiness for work. However, improving digital competencies and soft skills is an urgent need for graduates to be able to compete at a global level. This study recommends increasing cooperation between vocational schools and industry and sustainable development in terms of human resources and infrastructure to respond to changes occurring in Industry 4.0 and Society 5.0.. Keywords: Vocational Education, Link and Match, Deep Learning, SMK curriculum, Society 5.0